Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa Melalui Pendekatan Metacognitive Guidence - Muhamad Zulfikar Mansyur; Aep Sunendar (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2020)
Mathematical problem solving abilities (KPMM) are important for junior high school students. The Metacognitive Guidance (MG) approach can be an alternative to improve KPPM. The method used in this research is a quasi-experimental design with a nonequivalent control group design. The population in this study were all students of class VIII SMP Negeri 1 Bandung. Then two classes were taken using purposive sampling technique as the sample. The instrument used was the KPMM test. The results showed that there was a significant increase in the mathematical problem solving abilities of students who took the MG approach learning compared to students who took conventional learning. Then based on the students' initial mathematical abilities, the results showed that at the initial high and moderate mathematical problem solving abilities of students who took the MG approach learning was better than students who took conventional learning, whereas in students the initial mathematical abilities were low there was no difference in increasing problem solving abilities mathematical significance who follow the MG approach learning compared with students who take conventional learning.